A Micropatterned Human‐Specific Neuroepithelial Tissue for Modeling Gene and Drug‐Induced Neurodevelopmental Defects. Issue 5 (6th January 2021) - Sahni, Geetika; Chang, Shu‐Yung; Meng, Jeremy Teo Choon; Tan, Jerome Zu Yao; Fatien, Jean Jacques Clement; Bonnard, Carine; Utami, Kagistia Hana; Chan, Puck Wee; Tan, Thong Teck; Altunoglu, Umut; Kayserili, Hülya; Pouladi, Mahmoud; et al.
Abstract: The generation of structurally standardized human pluripotent stem cell (hPSC)‐derived neural embryonic tissues has the potential to model genetic and environmental mediators of early neurodevelopmental defects. Current neural patterning systems have so far focused on directing cell fate specification spatio‐temporally but not morphogenetic processes. Here, the formation of a structurally reproducible and highly‐organized neuroepithelium (NE) tissue is directed from hPSCs, which recapitulates morphogenetic cellular processes relevant to early neurulation. These include having a continuous, polarized epithelium and a distinct invagination‐like folding, where primitive ectodermal cells undergo E‐to‐N‐cadherin switching and apical constriction as they acquire a NE fate. This is accomplished by spatio‐temporal patterning of the mesoendoderm, which guides the development and self‐organization of the adjacent primitive ectoderm into the NE. It is uncovered that TGF β signaling emanating from endodermal cells support tissue folding of the prospective NE. Evaluation of NE tissue structural dysmorphia, which is uniquely achievable in the model, enables the detection of apical constriction and cell adhesion dysfunctions in patient‐derived hPSCs as well as differentiating between different classes of neural tube defect‐inducing drugs. Abstract : This paper reports the generation of a reproducible and highly organized neuroepithelial (NE) tissue by combining human pluripotent stem cell (hPSC) micropatterning and a temporally sequenced induction protocol to specify NE cells in spatial juxtaposition to mesoendoderm cells. By evaluating NE tissue structural dysmorphia in the micropatterned NE model, we can successfully model gene‐ and drug‐induced neurodevelopmental defects.